POST-PANDEMIC LEARNING SUSTAINABILITY: USING CANVAS INSTRUCTURE LEARNING MANAGEMENT SYSTEM IN ENGLISH CLASSES - Pratika, Dellis (STKIP Persada Khatulistiwa Sintang, 2025)
Canvas Instructure is a web-based LMS used in universities, mainly in North America, even before the COVID-19 outbreak 2020. The pandemic forces higher education to adapt to a new way of learning, and Canvas has increasingly been popular to facilitate online teaching and learning processes worldwide. However, it is relatively new to Indonesian higher education. Therefore, this research aims to describe the perception of a lecturer teaching English classes and the students using Canvas in an Indonesian university to sustain their post-pandemic learning. The researcher used a qualitative design with an interview and a focused group discussion. The data about the challenges, benefits, and expectations were obtained from observation and discussion with an English lecturer and students as the Canvas users. From the lecturer's perspective, Canvas can assist the users in designing organized modules, giving transparent grading, reusing courses, using less paper, and so on. However, when designing the course, the lecturer spent a lot of time. Therefore, the lecturer expects to collaborate with others in designing the course. As for the students, the challenge primarily lies in the Internet connection. On the other hand, it allows time and place flexibility, unlimited attempts, transparent rubrics, and grades, and many more. They expect all the English lecturers to use Canvas and to lessen the handwriting assignments. However, there are limitations to the data as the sample may not reflect or represent the views in a population and it is only relevant to the participants who share the common concerns or experiences.